Concept Analysis of Well-Being in Older Adults - Hongthai, Kerdsiri (Journal of Thailand Nursing and Midwifery Council, 2021)
This study using hybrid models of Schwartz-Barcott and Kim to analysis concept of well-being in older adults. The primary objective of the study was to analyse attributes of well-being as determined by older adults in terms of its antecedents and consequences. The study was conducted in three stages. The theoretical stage involved an integrated review of literature. Next, the field study stage was conducted using in-depth interviews of 27 older adults in both urban and rural areas, to obtain empirical data. Each informant was interviewed twice, each session lasting about 30 minutes. The final stage was devoted to content analysis and thematic analysis. According to the analysis, wellbeing as perceived by the older adults could be defined as incorporating life satisfaction, self-esteem, good health, happiness, and life goals. The following were identifed by the older adults as attributes of well-being: 1) awareness of life circumstances; 2) life valuing; 3) life satisfaction; 4) self-care capacity; 5) social activity capacity; 6) good quality of life; and 7) balance between needs and responses to them. Two major factors were identifed as antecedents to well-being: 1) intrapersonal factors (namely, self-acceptance, autonomy, self-built delight, and peace of mind) and 2) interpersonal factors (namely, respectability, mutual reliance, social acceptance, and family harmony). Consequences of well-being were considered to include: 1) self-care capacity; 2) good interpersonal relationship; 3) awareness of the quality of life; 4) life goals; 5) ability to contribute to the family and society; and 6) behavioral competence. The viewpoints of the older adults in this study concerning wellbeing could be applied to the planning of health care programmes for older adults. Emphasis should be placed on building constructive relationships within the family, to promote wellbeing and better quality of life in older adults in accord with their perception.